First, we rewrite the system of equations:
-8 - 7y = 11 (1)
7x + 3y = 6 (2)
To eliminate y, we can multiply equation (2) by 7 and equation (1) by 3, so that we can add them together:
-24 - 21y = 33 (3) (Multiply equation (1) by 3)
49x + 21y = 42 (4) (Multiply equation (2) by 7)
Now, add equations (3) and (4) together:
49x - 24 = 75
49x = 99
x = 99/49
x = 2
To solve for y, we can substitute the value of x back into either equation (1) or (2). Let's substitute x = 2 into equation (2):
7(2) + 3y = 6
14 + 3y = 6
3y = -8
y = -8/3
y = -2.67
Therefore, the solution to the system of equations is:
x = 2
y = -2.67
solve the system of linear equations using elimination with ADDITION, using addition.
-8 - 7y = 11
7x + 3y = 6
x =
y =
1 answer